1975
DOI: 10.1029/jb080i020p02931
|View full text |Cite
|
Sign up to set email alerts
|

Noble gases in Thailand tektites

Abstract: The abundance pattern of noble gases in Thailand tektites shows an anomalous spike of neon, apparently from the diffusion of atmospheric neon through the glass. The isotopic compositions of non‐radiogenic Ne, Ar, Kr, and Xe are atmospheric, but the Ar/Xe and Kr/Xe ratios in the tektites are each about an order of magnitude lower than the values in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
2

Year Published

1975
1975
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 23 publications
3
17
2
Order By: Relevance
“…They determined the diffusion coefficient of Ne in the glasses and suggested that Ne diffusion into solid was the main cause of Ne enrichment. Similar Ne enrichments were also reported for submarine glasses (Dymond and Hogan, 1973;Ozima and Zashu, 1983), tektites (Hennecke et al, 1975;Matsuda et al, 1993), impact glasses and obsidian (Miura and Nagao, 1991). This sug gests that the Ne enrichment seems to be a general feature for terrestrial natural glasses.…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…They determined the diffusion coefficient of Ne in the glasses and suggested that Ne diffusion into solid was the main cause of Ne enrichment. Similar Ne enrichments were also reported for submarine glasses (Dymond and Hogan, 1973;Ozima and Zashu, 1983), tektites (Hennecke et al, 1975;Matsuda et al, 1993), impact glasses and obsidian (Miura and Nagao, 1991). This sug gests that the Ne enrichment seems to be a general feature for terrestrial natural glasses.…”
Section: Introductionsupporting
confidence: 69%
“…Isotopic compositions of Ne in tektites and impact glasses agree very well with that of air, suggesting that Ne in these samples are atmo spheric in origin (Hennecke et al 1975;. The high 20Ne concentration in tektite is due to vesicles in tektite rather than the entrapment in the tektite glass itself, because Ne concentrations in tektites were much higher than those estimated from equilibrium solubility between air and silicate glass .…”
Section: Introductionsupporting
confidence: 55%
“…Matsuda et al (1989) measured noble gas contents in Darwin impact glasses and found significant enrichments of neon compared to air. Neon enrichments have been recorded from silica-rich glasses, such as tektites (Hennecke et al 1975;Matsuda et al 1993;Palma et al 1997), impact glasses (Matsuda et al 1989;, and obsidians (Matsuda et al 1989;Miura and Nagao 1991). A laboratory study clearly demonstrated that these neon enrichments are due to the faster diffusion of neon, compared with the heavier noble gases, in glasses after solidification (Matsubara and Matsuda 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The altitude estimated from the . Normal tektites (closed symbol) are from the Australasian strewn fields: thailandites (closed triangles: Hennecke et al 1975;Matsuda et al 1993), indochinites from Vietnam (closed circles: Matsuda et al 1993), and australites (closed triangles: Matsuda et al 1993). These data were obtained by heating of bulk samples.…”
Section: Implications For the Formation Of The Muong Nong-type Tektitesmentioning
confidence: 99%
See 1 more Smart Citation